Book review: Enghel, F. and Noske-Turner, J., editors. 2018: Communication in international development: Doing good or looking good?. (January 2020) - Srinidhi, Arjuna
Enghel, F. and Noske-Turner, J., editors. 2018: Communication in international development: Doing good or looking good? London, UK: Routledge. 198 pp. £31.99 (paperback), £110.00 (hardback). ISBN: 9781138569928 (paperback), ISBN: 9781138569911 (hardback).